Proposta de um sistema para o monitoramento de parques urbanos em fundos de vale - Martins, Larissa Fernanda Vieira; Venturi, Luis Antonio Bittar; Wingter, Giovanna Belem [UNESP] (FapUNIFESP (SciELO), 2019)
Urban parks must have physical, ecological and social functions. To achieve these functions, monitoring is necessary. This article aims to propose a protocol for monitoring valley-bottom parks. It was developed a metric system through indicators that allow for identifying if the park fulfills the functions and if there is conciliation. The indicators were segregated in two categories: i) Conservation and ii) Public Use. A score was composed for the final grade of each category (Conservation - IC and Public Use - IUP) between 0 and 10, which indicates the achievement degree of the function. The values obtained for IC and IUP were matched in a matrix of conciliation between the functions. For validation, the method was applied in the park Nascentes do Belém, in Curitiba, Brazil. The system demonstrated to be efficient at identifying if the park fulfills the functions, if conciliation occurs, and inferring priority areas to management.
Keywords: Environmental indicators; Environmental monitoring; Urban park; Valley-bottom